Arsenic distribution and phosphorus dynamics in saline soils of the dried Aral Sea bed: Implications for land degradation and soil management - Allaberdiev, Rustamjon; Jabbarov, Zafarjon; Abdurakhmonov, Nodirjon; Sherimbetov, Vafabay; Ziyadov, Shuqurillo; Abdurakhmanova, Mukaddas; Nomozov, Urol; Yagmurova, Dilafruza; Zafarjonov, Nurmukhammad; Abdullaev, Shokhrukh (Journal of Degraded and Mining Lands Management, 2026)
Arsenic (As) contamination in soils is a major environmental concern, particularly in saline and arid regions. The dried Aral Sea represents a unique environment where newly formed soils exhibit complex geochemical behavior. However, the interaction between arsenic and phosphorus (P) in these soils remains insufficiently understood. This study aimed to assess the concentration, spatial variability, and geochemical behavior of arsenic and its interaction with phosphorus in soils of the eastern part of the dried Aral Sea bed. A total of 25 soil samples were collected and analyzed for key physicochemical properties, including electrical conductivity (EC), available phosphorus (P?O?), cation exchange capacity (CEC), and arsenic content. Statistical analyses, including descriptive statistics and ANOVA, were applied. The results showed high spatial variability of soil properties. EC ranged from 1.75 to 13.70 dS/m (mean 7.05), indicating saline conditions. Arsenic concentrations varied from 14.90 to 181.80 (mean 100.99), while available phosphorus ranged from 4.40 to 23.99 mg/kg. ANOVA confirmed highly significant differences among all parameters (p < 0.0001). A strong interaction between arsenic and phosphorus was identified, with increased arsenic levels associated with reduced phosphorus availability due to competitive adsorption. These findings indicate that soils of the dried Aral Sea bed are highly heterogeneous and environmentally unstable. The results highlight the importance of effective soil management strategies to mitigate arsenic toxicity and improve nutrient availability in saline environments.